(untitled) (International Journal of Innovative Technologies in Economy, 2018)
In the article, from the standpoint of market conditions for the formation of labor demand and supply on qualified human resources, the existing problems of unregulated interaction of a plurality of enterprises of branches of the national economy of Ukraine with a number of higher educational institutions as consumers and suppliers of these resources are considered. The conditions and the scheme of organization of direct interaction of enterprises and educational establishments in the mode of "subject-subject" in the processes of ordering-training-supplying the necessary categories of human resources by minimizing the financial participation of the state budget and the managerial influences of the state are proposed and substantiated. It has been demonstrated that if a new scheme of cluster organization of relations between the subjects of supply and consumption of skilled human resources takes place on the labor market, the advantages of using the proposed organizational decisions from the standpoint of increasing the economic independence of the market participants, the possibilities of increasing the economic efficiency of their relations and, as a consequence, a reduction in the burden on the state budget.